2017
DOI: 10.1175/jcli-d-16-0697.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Winter North Atlantic Extratropical Cyclones in High-Resolution Regional Pseudo–Global Warming Simulations

Abstract: The present study investigates changes in the location, frequency, intensity, and dynamical processes of North Atlantic extratropical cyclones with warming consistent with the IPCC Fifth Assessment Report (AR5) representative concentration pathway 8.5 (RCP8.5) scenario. The modeling, analysis, and prediction (MAP) climatology of midlatitude storminess (MCMS) feature-tracking algorithm was utilized to analyze 10 cold-season high-resolution atmospheric simulations over the North Atlantic region in current and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 79 publications
21
77
0
Order By: Relevance
“…However, there exist regional variations in ETC changes and uncertainties among global climate models. Colle et al (2013) and Michaelis et al (2017) investigated future ETC changes more regionally for a subset of global models from the Coupled Model Intercomparison Project5 (CMIP5; Taylor et al 2012) for the representative concentration pathway (RCP) 8.5 scenario and found an increase in ETC track density immediately off the U.S. East Coast in the early to late twenty-first century. However, in contrast to Colle et al (2013), Michaelis et al (2017) showed that the density increase is not statistically significant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there exist regional variations in ETC changes and uncertainties among global climate models. Colle et al (2013) and Michaelis et al (2017) investigated future ETC changes more regionally for a subset of global models from the Coupled Model Intercomparison Project5 (CMIP5; Taylor et al 2012) for the representative concentration pathway (RCP) 8.5 scenario and found an increase in ETC track density immediately off the U.S. East Coast in the early to late twenty-first century. However, in contrast to Colle et al (2013), Michaelis et al (2017) showed that the density increase is not statistically significant.…”
Section: Introductionmentioning
confidence: 99%
“…Colle et al (2013) and Michaelis et al (2017) investigated future ETC changes more regionally for a subset of global models from the Coupled Model Intercomparison Project5 (CMIP5; Taylor et al 2012) for the representative concentration pathway (RCP) 8.5 scenario and found an increase in ETC track density immediately off the U.S. East Coast in the early to late twenty-first century. However, in contrast to Colle et al (2013), Michaelis et al (2017) showed that the density increase is not statistically significant. This is consistent with Zhang and Colle (2018), who showed that the ETC increase along the U.S. East Coast is sensitive to the model(s) used in the analysis, since some models have weaker or stronger storms depending on the differences in the baroclinicity and amount of latent heating predicted or resolved by the model.…”
Section: Introductionmentioning
confidence: 99%
“…Lenderink and Attema (2015) developed future scenarios of local precipitation events by perturbing the temperature and humidity boundary conditions of simulations in the regional models RACMO2 and HARMONIE, in order to mimic a 2 • C warmer world. A similar method is the "pseudo-globalwarming" method, which involves the simulation of observed events modifying the meteorological forcing by a climate change difference (Schär et al, 1996;Michaelis et al, 2017). For example, Trapp and Hoogewind (2016) applied climate change differences from CMIP5 (Coupled Model Intercomparison Project Phase 5) simulations on the highresolution Weather Research and Forecasting (WRF) model to reveal how typically observed extreme tornadoes might be realized under conditions of the late 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies suggest there will be a future decrease in the frequency of extratropical cyclones over the North Atlantic (Bengtsson et al, 2006;Chang, 2013;Zappa et al, 2013), although little decrease near the coast (Colle et al, 2013). Some studies have shown an increase in intensity for extratropical cyclones over the next 100 years (Marciano et al, 2015;Michaelis et al, 2017) resulting from additional condensational heating in a warmer (and more moist) climate; however, not all models agree with this change (Seiler and Zwiers, 2016). There is currently little understanding of how hybrid storms like Sandy will change in the future, and more work is needed looking at tropical and extratropical cyclone changes as well.…”
Section: Future Storm Tide Flooding Npccmentioning
confidence: 99%
“…With regard to extratropical cyclones, most studies suggest there will be a future decrease in their frequency over the North Atlantic (Bengtsson et al, 2006;Chang, 2013;Zappa et al, 2013), although little decrease near the coast (Colle et al, 2013). Some studies have found that there will be an increase in intensity for extratropical cyclones over the next 100 years over the northern Atlantic (Marciano et al, 2015;Michaelis et al, 2017) resulting from additional condensational heating in a warmer (and more moist) climate; however, not all models agree with this change (Seiler and Zwiers, 2016). Extratropical cyclones that cause wind extremes tend to follow a preferred track (Booth et al, 2015), and cli-mate models suggest that there has been an increase in the occurrence of strongly intensifying cyclones along this preferred track (Colle et al, 2013).…”
Section: Recommendations For Researchmentioning
confidence: 99%